Evaluación del crecimiento, sobrevivencia y calidad de una plantación de Hevea brasiliensis “shiringa” del CIEFOR – Puerto Almendra, Loreto – Perú. 2022 - Hernandez Zevallos, Llensy Lisbeth (2024)
The study was carried out in Forest Plot No. 31 of 1 hectare in CIEFOR - Puerto Almendra, 102 Hevea brasiliensis plants were evaluated. The objective of the study was to determine the increase in diameter and height, the survival, mortality and quality of the plants. The plantation presented an average increase in diameter of 3.17 mm and an average increase in height of 20.51 cm. The research hypothesis is rejected, indicating that the growth in diameter and height of the plants do not present statistical difference. There was a mortality of 49% (98 dead plants) and 51% survival (102 live plants). The highest number of seedlings is presented by the Regular quality with 79 seedlings that represents 77.5% of the total number of living plants, followed by the Good quality with 20 living individuals that represent 20.0% and, finally, the least number of individuals. They were observed in the Good quality with 3 seedlings that represented 2.9% of the total. At the general experimental level, a quality coefficient that varies from bad to regular was recorded. It is necessary to continue with the evaluations in plot No. 31 of Hevea basiliensis in CIEFOR - Puerto Almendra.